Moments and an integral representation for the non-symmetric Dunkl-classical form - Habbachi, Y. (Methods of Functional Analysis and Topology, 2022)
In this paper, we determine the moments and an integral representation for the non-symmetric Dunkl-classical form. Знайдено моменти та інтегральне представлення для несиметричної класичної за Данклом форми.